Ex-situ Conservation of some Endemic and Threatened Plant Species of India - Goel, A. K.; Mamgain, S. K. (Indian Forester, 2001)
Plant diversity in Indian subcontinent is under threat mainly due to human activities and reproductive isolation of the species. It is estimated that 15-20 per cent of our vascular flora i.e. about 2,500 species of plants are under various degrees of threat of which about 1,000 species are native to tropical and subtropical regions of the country. The increasing loss of plant diversity has turned the attention of various agencies to take the immediate conservation measures and save it from further depletion and extinction. Besides protection of species in-situ, the off-site (ex-situ) conservation of species particularly of those which are rare and endangered, has become an important tool for conservation of biological diversity. Considering the urgency for conservation of plant diversity we have taken up the task of ex-situ conservation of some tropical and subtropical threatened plant species of India in the N.B.R.I. Botanic Garden. The main aim of this work is to acclimatise, cultivate, propagate and multiply such taxa under ex-situ condition and subsequently reintroduce them to natural or semi-natural habitats together with maintenance of the species ex-situ in the botanic garden.